Unveiling the UNESCO Biosphere Reserve of the Berlengas Archipelago in Portugal as a Hotspot of Fish Species Using eDNA Metabarcoding and the Collaboration of Fishing Crews - Marco Simões; Cátia Costa; Maria da Luz Calado; Nuno Vasco-Rodrigues; Maria Jorge Campos; Sérgio Miguel Leandro; Agostinho Antunes (Journal of Marine Science and Engineering)
Managing fishery resources is crucial to ensure the marine environment continues to provide diverse goods and services. To overcome difficulties of classical methods used for fish stock management, molecular tools have shown potential to address this issue assessing both targeted and non-targeted species. This study aims to evaluate the spatiotemporal diversity of fish using 12S rRNA gene eDNA metabarcoding sequencing in the Berlengas archipelago and compare two seawater eDNA sampling sources: samples collected by fishermen during their activities and those collected by our research team. The results indicated that autumn presented the highest diversity and that the area around Berlenga Island was the richest area, increasing biodiversity across the region. Fisher-collected samples were generally less diverse than those by the research team but detected species typical of deeper and open-ocean habitats, validating this sampling method. Our study also highlighted eDNA’s role in monitoring fish species by detecting unexpected species for the region, such as Atlantic salmon (Salmo salar) and Atlantic cod (Gadus morhua), while cautioning against false positives like orange clownfish (Amphiprion percula) and blue tilapia (Oreochromis aureus). Future optimisation of our eDNA sampling methodology could better refine marine ecosystem dynamics around the UNESCO Biosphere Reserve of the Berlengas Archipelago, Portugal.